Analyzing Gender Injustice in Indonesia: Legal and Civic Education Perspectives - Muh. Amar; Andi Kasmawati; Mustaring Mustaring; Bakhtiar Bakhtiar; Ahmadin Ahmadin (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
Gender injustice in Indonesia is a structural social problem and is legitimized by cultural norms and legal systems that have not fully sided with equality between women and men. This research aims to analyze the problem of gender inequality that occurs systemically despite the existence of a legal framework that supports justice, as well as examine how legal and civic education can contribute to social transformation towards a more gender-just society. The focus of the study includes three things: (1) the concept of gender and forms of gender injustice which include marginalization, subordination, stereotypes, gender-based violence, and double burden; (2) gender justice in the legal system and the challenges of its enforcement in Indonesia; and (3) the role and barriers of legal and citizenship education in encouraging citizens' critical awareness of gender justice issues. This study uses a normative legal method with a descriptive-analytical approach, which focuses on legal regulations related to gender justice, protection of women's rights, and analysis of the role of legal education and citizenship in fighting for gender justice. The results of the study show that although Indonesia has ratified various national and international legal instruments that regulate gender justice, implementation on the ground is still hampered by patriarchal culture, low gender-based legal literacy, and structural bias in law enforcement institutions. On the other hand, legal and civic education has strategic potential as a means of social change, but until now it has not been optimal in integrating gender perspectives substantively in curriculum, pedagogy, and institutional practices. Therefore, education reform that is more progressive and responsive to gender issues is needed as part of efforts to build citizens who are inclusive, critical, and uphold the values of justice.